2003
DOI: 10.1046/j.1365-8711.2003.06368.x
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium fractionation on interstellar grains studied with the direct master equation approach

Abstract: We have studied deuterium fractionation on interstellar grains with the use of an exact method known as the direct master equation approach. We consider conditions pertinent to dense clouds at late times when the hydrogen is mostly in molecular form and a large portion of the gas‐phase carbon has already been converted to carbon monoxide. Hydrogen, oxygen and deuterium atoms, as well as CO molecules, are allowed to accrete on to dust particles and react there to produce various stable molecules. The surface ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 12 publications
1
66
0
Order By: Relevance
“…We included the major gaseous D-exchange reactions of the UMIST database (McElroy et al 2013), the major surface reactions identified by Stantcheva & Herbst (2003), and gas-phase reactions related to HDO using the approach of Aikawa et al (2012). The initial chemical abundances were adopted from Garrod et al (2007), and include the initial abundance [HD] = 1.5 × 10 −5 × [H 2 ] (Osamura et al 2005).…”
Section: Chemical Modeling Of Abundancementioning
confidence: 99%
“…We included the major gaseous D-exchange reactions of the UMIST database (McElroy et al 2013), the major surface reactions identified by Stantcheva & Herbst (2003), and gas-phase reactions related to HDO using the approach of Aikawa et al (2012). The initial chemical abundances were adopted from Garrod et al (2007), and include the initial abundance [HD] = 1.5 × 10 −5 × [H 2 ] (Osamura et al 2005).…”
Section: Chemical Modeling Of Abundancementioning
confidence: 99%
“…Therefore, it is not suitable for incorporation in codes that include complex networks of grain-surface reactions. In addition to the master equation method, a Monte Carlo method was proposed by Article published by EDP Sciences Tielens & Hagen (1982) and applied to interstellar modelling by Charnley (2001), Caselli et al (2002), and Stantcheva & Herbst (2003). Cuppen & Herbst (2005) developed random walk models for molecular hydrogen formation on grains that take into account the effect of surface roughness on the diffusion and reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Presently published grain chemistry models predict an HDO fractionation of about 40% (i.e. almost all the deuterium would be locked in HDO) if deuterated water forms on the grain surfaces at the same time as formaldehyde and methanol (Caselli et al 2002;Stantcheva & Herbst 2003).…”
Section: Introductionmentioning
confidence: 99%